Spatiotemporal Variability of Microplastics in the Eastern Baltic Sea - Mishra, Arun; Buhhalko, Natalja; Lind, Kati; Lips, Inga; Liblik, Taavi; Väli, Germo; Lips, Urmas (Frontiers in Marine Science, 2022)
Microplastic (MP) pollution is present in all aquatic environments and is gaining critical concern. We have conducted sea surface MP monitoring with a Manta trawl at 16 sampling stations in the eastern Baltic Sea in 2016–2020. The concentrations varied from 0.01 to 2.45 counts/m3 (0.002–0.43 counts/m2), and the mean was 0.49 counts/m3 (0.08 counts/m2). The fibers and fragments had, on average, an approximately equal share in the samples. Correlation between the concentration of fibers and fragments was higher near the land and weaker further offshore. The following spatial patterns were revealed: higher mean values were detected in the Baltic Proper (0.65 counts/m3) (0.11 counts/m2) and the Gulf of Finland (0.46–0.65) (0.08–0.11) and lower values were detected in the Gulf of Riga (0.33) (0.06) and Väinameri Archipelago Sea (0.11) (0.02). The difference between the latter three sub-basins and the meridional gradient in the Gulf of Riga can likely be explained by the degree of human pressure in the catchment areas. The MP concentration was higher in autumn than in summer in all regions and stations, probably due to the seasonality of the biofouling and consequent sinking rate of particles. A weak negative correlation between the wind speed and the MP concentration was detected only in the central Gulf of Finland, and positive correlation in the shallow area near river mouth. We observed a 60-fold difference in MP concentrations during coastal downwelling/upwelling. Divergence/convergence driven by the (sub)mesoscale processes should be one of the subjects in future studies to enhance the knowledge on the MP pathways in the Baltic Sea.